Mirror Neuron dalam Proses Empati Manusia kerusakan / Disfungsi yang Terjadi pada Mirror Neuron - Elvaretta, Maria Leony; Dhuha, Nurul Azizah; Zefanya, Natasha; Tara, Lativa; Pradnyandari, Ni Nyoman Putri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Humans are essentially created as social creatures and need each other to interact with each other. Human life coexists with other humans, so social interaction cannot be avoided. As humans, we must be sensitive and respectful of each other. One of the social interaction capitals is the ability to empathize. Empathy can be defined as when an individual can feel what others feel, and this can be explained from a neuroscience perspective. The mirror neuron is one of the small parts of the brain that has the primary function as a mirror within the individual, in other words it is the center of the process where empathy occurs. The purpose of this study is to investigate the function of mirror neurons that are closely related to human empathy processes and the damage or dysfunction that occurs in it. Through literature studies, it is known that the mirror neurons are located in some parts of brain structures; in the premotor area and the lower parietal cortex. Mirror neurons generally project events around the individuals so the emotions and such behaviors are felt by the individuals. The lack of empathy experienced by some individuals with psychopathy as well as difficulty in understanding situations or responding to social cues in children with Autism Spectrum Disorder (ASD) can be due to the dysfunction in mirror neurons. However, mirror neurons dysfunction still requires further research to be able to understand the role of mirror neurons in various aspects of mental processes and human behavior.